2011
DOI: 10.1371/journal.pone.0026891
|View full text |Cite
|
Sign up to set email alerts
|

Does Reduced IGF-1R Signaling in Igf1r+/− Mice Alter Aging?

Abstract: Mutations in insulin/IGF-1 signaling pathway have been shown to lead to increased longevity in various invertebrate models. Therefore, the effect of the haplo- insufficiency of the IGF-1 receptor (Igf1r+/−) on longevity/aging was evaluated in C57Bl/6 mice using rigorous criteria where lifespan and end-of-life pathology were measured under optimal husbandry conditions using large sample sizes. Igf1r+/− mice exhibited reductions in IGF-1 receptor levels and the activation of Akt by IGF-1, with no compensatory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
126
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 47 publications
6
126
2
1
Order By: Relevance
“…The Interventions Testing Program, designed to test the reproducibility of lifespan studies at multiple testing sites, has validated eight treatments that extend lifespan; seven are unique to one sex. Our lifespan extension in the IGF-1-deficient female mice mirrors the haploinsufficiency of igfr study performed by the Richardson laboratory, where females showed a modest increase in lifespan that was not evident in males (Bokov et al 2011). The mechanism(s) underlying the sexual dimorphism of lifespan studies, including those with IGF-1 deficiency, are still largely unknown.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The Interventions Testing Program, designed to test the reproducibility of lifespan studies at multiple testing sites, has validated eight treatments that extend lifespan; seven are unique to one sex. Our lifespan extension in the IGF-1-deficient female mice mirrors the haploinsufficiency of igfr study performed by the Richardson laboratory, where females showed a modest increase in lifespan that was not evident in males (Bokov et al 2011). The mechanism(s) underlying the sexual dimorphism of lifespan studies, including those with IGF-1 deficiency, are still largely unknown.…”
Section: Discussionsupporting
confidence: 69%
“…Although this study has been routinely cited in the literature as evidence that IGF-1 signaling in mammals is detrimental to both healthspan and lifespan, the short lifespan of the control animals in this study (∼750 days) compromise interpretation. Follow-up studies where control animals exhibited a normal lifespan did not result in a dramatic extension of lifespan and females exhibited a modest 5-10% increase in lifespan whereas no increase was observed in response to IGF-1 deficiency in males (Bokov et al 2011;Xu et al 2014). The studies detailed here clearly demonstrate that deficiencies in circulating IGF-1 beginning at or before 5 months of age result in a 15% increase in lifespan in females and that decreases in IGF-1 occurring later in life have little effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, brain-specific overexpression of IGFBP-6 causes glucose intolerance and insulin resistance both on a control diet and on a high-fat diet and promotes increased weight gain (3). As mentioned above, reduction of IGF-I signaling by reducing levels of IGF-I receptors has also been associated with impairments in glucose metabolism under both normal and high-fatfed conditions (4,19,21). Conversely, mice lacking IGFBP-3, -4, and -5, and thus displaying increased levels of IGF-I, show significant enhancement in several measurements of glucose metabolism, including glucose tolerance (31).…”
Section: Discussionmentioning
confidence: 97%
“…However, this relationship has been less clearly defined in models in which IGF-I signaling has been targeted directly. In independent studies, reduction of the cellular receptor of IGF-I (IGF-IR) in mice has been reported to extend lifespan in female but not male mice (4,21). Interestingly, both studies also reported a significant impairment in glucose metabolism in male mice that was not generally found in female mice.…”
mentioning
confidence: 99%
“…This is not the first time a study was unable to replicate the increase in lifespan shown in an original study. For example, knockout mouse models for the signaling molecule p66Shc (p66shc −/− mice) (Migliaccio et al., 1999), insulin receptor substrate 2 (Irs2) (Irs2 +/− mice) (Taguchi, Wartschow & White, 2007), and the IGF1 receptor ( Igf1r +/− mice) (Holzenberger et al., 2003) all showed substantial lifespan extension in initial reports that was not confirmed in follow‐up studies (Bokov et al., 2011; Ladiges et al., 2009; Liang et al., 2003 ; Ramsey et al., 2014; Selman, Lingard, Gems, Partridge & Withers, 2008; Selman et al., 2007; Unnikrishnan, Deepa, Herd & Richardson, 2017). Differences in genetic background can potentially modulate lifespan results.…”
Section: Discussionmentioning
confidence: 99%